Surgical Treatment of Retrograde Peristalsis Following Laparoscopic Roux-en-Y Gastric Bypass - Sanders, Christina M. (Society of Laparoendoscopic Surgeons, 2012)
BACKGROUND: Retrograde Roux limb peristalsis following laparoscopic Roux-en-Y gastric bypass is a rare complication that can be difficult to identify. It may present as persistent nausea, vomiting, abdominal pain, or even gastrointestinal bleeding related to an anastomotic ulcer. Upper gastrointestinal (UGI) series is an important diagnostic modality to identify this motility disorder; however, it may not be readily identifiable without specific delayed imaging. The etiology of this phenomenon is unclear, but attributing factors include the presence of ectopic pacemaker cells, variable lengths of the Roux limb and misconstructions. When this problem is identified, revisional surgery is indicated. CASE DESCRIPTION: A 51-y-old female with morbid obesity presented with persistent nausea and vomiting following a laparoscopic gastric bypass. A CT scan showed a dilated Roux limb. Reverse peristalsis from the jejunojejunostomy toward the gastric pouch was identified on a UGI. Two laparoscopic revisions of the jejunojunostomy were attempted to correct this dysfunction. DISCUSSION: An attempt at widening and relaxing the anastomosis was unsuccessful at providing relief of symptoms. A second revision with an anastomosis between the Roux limb and common channel provided long-term improvement. Identifying complications of gastric bypass surgery can be challenging. Imaging studies may be limited, and often diagnostic and revisional surgery is indicated.